Effects of adding cracked corn to a pelleted supplement for nursery and finishing pigs - Paulk, C.B.; Fahrenholz, Adam C.; Wilson, J.M.; Cook, D.D.; McKinney, Leland J.; Ebert, J.C.; Ohlde, J.J.; Nietfeld, Jerome C.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Three experiments were conducted to determine the effects of supplementing cracked corn into diets of nursery and finishing pigs. In Exp. 1, 144 pigs were used in a 28-d trial. Pigs (PIC TR4 × 1050; initially 16.5 lb) were weaned and allotted with 6 pigs per pen (3 barrows and 3 gilts) and 6 pens per treatment. All pigs were fed a common diet for 7 d postweaning and the experimental diets for the next 28 d. Treatments were corn-soybean meal-based in the form of mash, pellets, and pellets with 100% of the corn either ground (618 μm) or cracked (3,444 μm) and blended into the diet after the rest of the formulation (the supplement) had been pelleted. Overall (d 0 to 28), ADG and F/G improved when pigs were fed the mash control compared to the pelleted diets (P < 0.001); however, this response was caused by the poor performance of pigs fed the supplement treatments, with the pigs fed the complete pellets having improved (P < 0.01) ADG and F/G compared with pigs fed the pelleted supplement blended with ground and cracked corn. Finally, pigs fed the supplement blended with cracked corn had numerically lower (P < 0.11) ADG and poorer (P < 0.001) F/G compared to those fed the supplement blended with ground corn. In Exp. 2, 224 nursery pigs (initially 16.3 lb) were used with 7 barrows or 7 gilts per pen and 8 pens per treatment. Treatments were corn-soybean meal-based and fed as mash, pellets, and pellets with 50% of the corn either ground (445 μm) or cracked (2,142 μm) and blended with the pelleted supplement. Pigs fed mash had improved (P < 0.03) ADG and F/G compared with pigs fed the other treatments; however, this resulted from adding ground or cracked corn outside the pellets (complete pellets vs. pelleted supplement with corn, P < 0.01). In Exp. 3, 252 finishing pigs (initially 88.2 lb) were used with 7 pigs per pen and 9 pens per treatment. The treatments were the same as Exp. 2. Pigs fed mash had lower (P < 0.004) ADG compared with pigs fed diets with pellets. Pigs fed complete pellets had improved (P < 0.03) ADG and F/G compared with pigs fed corn and the pelleted supplement. Also, pigs fed the supplement blended with cracked corn had greater (P < 0.02) ADG than pigs fed the supplement blended with ground corn. Pelleting the diet led to an increase (P < 0.05) in ulceration scores; however, these negative effects on ulcer scores were reduced (P < 0.001) by cracking 50% of the corn and adding it postpellet.
Keywords: Swine; Corn; Cracked corn; Feeding processing; Pelleting; Nursery pig; Finishing pig